Faktor-Faktor Yang Mempengaruhi Minat Siswa Untuk Melanjutkan Pendidikan Di Perguruan Tinggi - Risma Febryanti (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This study aims to determine the factors that influence students' interest in continuing their education in tertiary institutions in class XI SMK students. The research design used in this study is quantitative. The sampling technique in this study used a proportional random sampling technique. The data collection technique was carried out using a closed questionnaire. Data analysis techniques in this study used descriptive statistical calculations. The results of this study are that internal factors have an influence on students' interest in continuing their education in tertiary institutions by 67% and external factors have an effect on students' interest in continuing their education in tertiary institutions by 44%.